Wandering spleen: Case report and literature review - Almarghoub, Mohammed A; Anwar, Ihab (Indian Journal of Case Reports, 2018)
The spleen is fixed in the left upper abdominal quadrant by various ligaments. Any ligament laxity or defect will result in a rare condition called “wandering spleen.”